An experimental evaluation of the impact of intensive supervision on the recidivism of high-risk probationers - Hyatt, Jordan M. (Crime & delinquency, 2017)
This article reports the results of an experimental evaluation of the impact of Intensive Supervision Probation (ISP) on probationer recidivism. Participants, who were assessed at an increased likelihood of committing serious crimes and not ordered to specialized supervision, were randomly assigned to ISP (n = 447) or standard probation (n = 385). ISP probationers received more restrictive supervision and experienced more office contacts, home visitations, and drug screenings. After 12 months, there was no difference in offending. This equivalence holds across multiple types of crimes, including violent, non-violent, property, and drug offenses, as well as in a survival analysis conducted for each offense type. ISP probationers absconded from supervision, were charged with technical violations, and were incarcerated at significantly higher rates. Policy implications for these results are discussed.